Monitoring of insecticide resistance in Spodoptera litura (Lepidoptera: Noctuidae) from four districts of Punjab, Pakistan to conventional and new chemistry insecticides. (January 2016) - Saleem, Muhammad; Hussain, Dilbar; Ghouse, Ghulam; Abbas, Muneer; Fisher, Susan W.
Abstract: Studies were carried out to evaluate the resistance of Pakistani populations of the beet armyworm, Spodoptera litura (F) to several commonly used insecticides. Different field populations of S. litura from four districts of the Punjab were monitored from 2009 to 2011 for resistance to insecticides using a standard leaf dip bioassay method. For organophosphates and pyrethroids, resistance ratios compared with a susceptible Lab-Pk population were in the range of 8–109 fold for deltamethrin, 11–139 fold for cypermethrin, 19–143 fold for chlorpyrifos and 39–162 fold for profenofos. For new chemistry insecticides, resistance levels were 2–74 fold for spinosad, 4–216 fold for abamectin, 7–87 fold for indoxacarb, 2–77 fold for emamectin benzoate, 1.9–58 fold for lufenuron and 4–43 fold for methoxyfenozide. Pairwise correlation coefficients of LC50 values showed a positive correlation with cross-resistance among deltamethrin, cypermethrin and chlorpyrifos, while resistance to profenofos showed correlations with resistances to other insecticides except chlorpyrifos. New chemistry insecticides showed no correlations between any of the tested insecticides. There were high to very high levels of resistance to organophosphates in most of the population, which suggested that the use of these should be avoided against this pest. Selective use of pyrethroids in several areas, including Bahawalpur and Lodhran, where the pest showed a low level of resistance, would appear to be acceptable, the new chemistry insecticides, lufenuron, methoxyfenozide, emamectin and indoxacarb had no, very low, low and moderate resistance levels against populations, respectively. These are considered to be safe to the environment and safer to natural enemies. Highlights: Spodoptera litura in Punjab, Pakistan had high level of resistance to pyrethroids. S. litura in Punjab, Pakistan had moderate to high level of resistance to organophosphate. S. litura in Punjab, Pakistan had very low level of resistance to IGRs. S. litura in Punjab, Pakistan had low to moderate level of resistance to Spinosad, emamectin benzoate, indoxacarb and abamectin.